Causation in Psychoanalysis - Axmacher, Nikolai (Frontiers in Psychology, 2013)
It has been argued that psychoanalytic and biological theories cannot be integrated because they rely on different epistemological grounds, namely on hermeneutic versus causal explanations, that are inconsistent with each other. Such inconsistency would seriously question the general possibility of neuropsychanalytic research. Here, I review three important arguments that have been raised in favour of this inconsistency: First, that psychoanalytic attempts to overcome repression aim to go beyond causal relationships; second, that hermeneutic explanations are retrospective and context-dependent and therefore follow a different logic than causal explanations; and third, that only causal hypotheses are falsifiable, while the introspective reasons for one’s own behaviour are not. I present arguments against each of these statements and show that actually, causal and hermeneutic explanations are, at least in principle, consistent with each other. The challenge for neuropsychoanalytic research remains to find indeed empirical examples of theories which are causal and hermeneutic at the same time.